2009
DOI: 10.1073/pnas.0902575106
|View full text |Cite
|
Sign up to set email alerts
|

Maternally invested carotenoids compensate costly ectoparasitism in the hihi

Abstract: Dietary ingested carotenoid biomolecules have been linked to both improved health and immunity in nestling birds. Here, we test whether maternally invested egg carotenoids can offset the cost of parasitism in developing nestling hihi (Notiomystis cincta) from the bloodsucking mite (Ornithonyssus bursa). Our results reveal clear negative effects of parasitism on nestlings, and that maternally derived carotenoids compensate this cost, resulting in growth parameters and ultimate mass achieved being similar to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…If brood hierarchies create stressful growth environments for later-hatched 362 nestlings, why did carotenoids not mitigate these effects? We know that our 363 supplementation changed the phenotype of nestlings, as previous analyses of subsets of 364 these data indicate differences in nestlings' body condition (Ewen et al 2009) and 365 tarsus length (Ewen et al 2008) at fledging, and here we find that carotenoid 366 supplementation leads to faster growth (at least for tarsi). Other work with hihi has also 367 shown that increased access to carotenoids influences nestling begging (Ewen et al…”
mentioning
confidence: 48%
See 3 more Smart Citations
“…If brood hierarchies create stressful growth environments for later-hatched 362 nestlings, why did carotenoids not mitigate these effects? We know that our 363 supplementation changed the phenotype of nestlings, as previous analyses of subsets of 364 these data indicate differences in nestlings' body condition (Ewen et al 2009) and 365 tarsus length (Ewen et al 2008) at fledging, and here we find that carotenoid 366 supplementation leads to faster growth (at least for tarsi). Other work with hihi has also 367 shown that increased access to carotenoids influences nestling begging (Ewen et al…”
mentioning
confidence: 48%
“…The sample sizes 160 for these analyses were limited by how many nests we were able to collect data on We fitted a standard logistic growth model (Ricklefs, 1968) using the SSlogis function of 179 the "stats" package in R (R Core Team, 2013) to estimate each individual's asymptotic 180 mass (g) and tarsus length (mm), and their growth rates (k). Logistic growth models fit 181 postnatal growth data well in passerines (Starck & Ricklefs, 1998), and have been used 182 to describe growth before in hihi (Ewen et al 2009). Nestlings that died before fledging 183 were excluded.…”
Section: Onset Of Incubation and Hatching Spread 155mentioning
confidence: 99%
See 2 more Smart Citations
“…The inaccessibility of the nests prevented us from determining the cause of nest failure. However, hihi nestling (Armstrong et al 2007;Ewen et al 2009;Rippon 2010). The improved success of feeder-using females is presumably due to supplementary feeding increasing nestling provisioning rates (Makan 2006).…”
Section: Discussionmentioning
confidence: 99%